Cyclopentannulated decacyclenes as carbon-based multistage electron acceptors - Eiden, Silas C.; Misselwitz, Erik; Rominger, Frank; Kivala, Milan (Chemistry, 2025)
We report a series of cyclopentannulated decacyclenes that act as remarkable multistage electron acceptors. The compounds were synthesized in a modular approach via Yamamoto cyclotrimerization of brominated pyracylene precursors, allowing the introduction of electron-withdrawing, -donating, and solubilizing fluoro, methoxy, and tert-butyl moieties, respectively. The subsequent π-expansion of the polycyclic scaffold was achieved by oxidative cyclodehydrogenation. X-ray crystallographic analysis revealed the propeller-shaped geometry of the decacyclene core with a pronounced bond length alternation in the central six-membered ring and the columnar packing motif in the solid state. Depending on the substitution pattern, the compounds are capable of up to six reversible reductions within a particularly narrow potential range between −1.45 and −2.86 V under electrochemical conditions. This result is in stark contrast to only two reductions of parent decacyclene and clearly demonstrates the major impact of strategic cyclopentannulation on the redox properties of the sp2-carbon scaffold, which was further supported by density functional theory studies.
Veröffentlicht: 10 June 2025
Gesehen am 20.10.2025